Review on current issue of clonal banana (Musa sp.) for yield improvement / Noor Maisarah Mohd Noor - Mohd Noor, Noor Maisarah (Faculty of Plantation and Agrotechnology, 2017)
Banana (Musa sp.) is one of the largest herbaceous flowering plant and become the fourth most important food crop in the world. The world production of banana was about 99 million tonnes annually which is mostly produced by tropical countries (FAO, 2003). The growth and yield of banana production are declining due to the abiotic and biotic stress. Thus plant tissue culture technology is used to overcome the problem. A review study was done by analyzing previous researchers‟ findings on the most proximate technique for tissue culture of banana. From the review paper, it can be concluded that the culture medium used is Murashige & Skoog (MS) medium with different concentrations of plant growth regulators and supplement. The rates of successful for tissue culture are mostly affected by the optimum value of supplement and plant growth regulator.